Analisis Kesiapan Guru dalam Mengimplementasikan Mata Pelajaran Koding dan Kecerdasan Artifisial pada Kurikulum Nasional di Sekolah Menengah - Gunawan Ekoran; Diesti Aspariga; Zulfitria Zaidir (Journal Innovation In Education, 2025)
The COVID-19 pandemic has driven the transformation of the education system, especially through the implementation of distance learning at various levels, including Senior High Schools (SMA). This study aims to analyze the evaluation and assessment strategies applied in the context of Distance Learning at the senior high school level. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation in three senior high schools in Tual City, Maluku. The results of the study show that teachers face a number of challenges in the evaluation process, especially related to assessment accuracy, academic integrity, and limitations of technological infrastructure. However, adaptive strategies were also found to be used by teachers, such as project-based assessment, online formative assessment, and the use of digital platforms to support the evaluation process. This strategy is considered effective in maintaining the quality of assessment amidst the limitations of online learning. This study recommends the importance of strengthening teacher training in the field of digital assessment, improving technological infrastructure, and developing adaptive and contextual evaluation policies to support the success of distance learning.